If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -12 = -11x + 9 Reorder the terms: -12 + -12x = -11x + 9 Reorder the terms: -12 + -12x = 9 + -11x Solving -12 + -12x = 9 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -12 + -12x + 11x = 9 + -11x + 11x Combine like terms: -12x + 11x = -1x -12 + -1x = 9 + -11x + 11x Combine like terms: -11x + 11x = 0 -12 + -1x = 9 + 0 -12 + -1x = 9 Add '12' to each side of the equation. -12 + 12 + -1x = 9 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 9 + 12 -1x = 9 + 12 Combine like terms: 9 + 12 = 21 -1x = 21 Divide each side by '-1'. x = -21 Simplifying x = -21
| -4x=0.8 | | N/2-9=-9 | | -31+x=4x+20 | | -4+10+6x=28 | | -12+8x=6x+28 | | 3/6=g/90 | | 6n^2-45n+84=0 | | -5x-39=57+x | | -18p=-9 | | xx+1=0 | | 4lnx=60 | | -34+9x=6x+53 | | -4=-16x | | 7/8=n | | -29-10x=-12x+25 | | 37=5p-3 | | -152-x=8x+55 | | 10x+19=3x+229 | | 10x+19=3x+22 | | -82-12x=-5x+65 | | 48=4n+20 | | x+6=4x^2-12x+9 | | -101-3x=-10x+39 | | -95+12x=6x+31 | | Y^2=14y-48 | | =2x+2 | | -39+6x=10x+17 | | 47=5m+2 | | 14+1/5=10 | | 20(14-4)-4(6-4)= | | -20-3x=6-2x | | 2z-4=-2 |